Pemanfaatan Sabun Eco-Enzyme sebagai Media Pemberdayaan ‎dan Edukasi Lingkungan Berkelanjutan - Ernilawati; Siti Munawarah Panggabean (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2025)
This study investigates the utilization of eco-enzyme soap as a medium for empowerment and sustainable environmental education, addressing the growing need for community-based approaches to environmental awareness and waste management in developing regions. Grounded in the principles of Education for Sustainable Development (ESD), the research aimed to explore how eco-enzyme soap production can function as both an educational innovation and a tool for socio-environmental empowerment. A participatory action research (PAR) design was employed, involving 25 purposively selected participants consisting of postgraduate students, teachers, and local community members in Palembang, Indonesia. Data were collected through observation, semi-structured interviews, and participatory workshops, then analyzed thematically using Braun and Clarke’s six-phase framework. The results reveal that the eco-enzyme initiative enhanced environmental literacy, strengthened community collaboration, and generated economic value through small-scale entrepreneurship while simultaneously reducing household waste. Participants demonstrated improved understanding of scientific concepts such as fermentation and enzyme activity, along with increased awareness of sustainable living and collective responsibility. The findings confirm that eco-enzyme projects not only serve as effective pedagogical models integrating theory and practice but also promote empowerment through active engagement, leadership, and gender-inclusive participation. This study concludes that the integration of eco-enzyme production into educational and community programs provides a transformative framework for linking environmental science, social innovation, and sustainability. The implications emphasize that eco-enzyme initiatives can be institutionalized as scalable models for green education and local empowerment, informing policy development, curriculum innovation, and future research on community-based sustainability practices across diverse socio-educational contexts.